2017
DOI: 10.1016/j.apm.2017.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Learning-based robust stabilization for reduced-order models of 2D and 3D Boussinesq equations

Abstract: a b s t r a c tWe present some results on the stabilization of reduced-order models (ROMs) for thermal fluids. The stabilization is achieved using robust Lyapunov control theory to design a new closure model that is robust to parametric uncertainties. Furthermore, the free parameters in the proposed ROM stabilization method are optimized using a data-driven multiparametric extremum seeking (MES) algorithm. The 2D and 3D Boussinesq equations provide challenging numerical test cases that are used to demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…(i) Closure Modeling: To model the effect of the discarded ROM modes, a Correction term is generally added to the standard ROM [3,29,32,37]. Given the drastic truncation used in ROMs for realistic flows, the Correction term is essential for accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(i) Closure Modeling: To model the effect of the discarded ROM modes, a Correction term is generally added to the standard ROM [3,29,32,37]. Given the drastic truncation used in ROMs for realistic flows, the Correction term is essential for accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…(iii) Data-Driven Modeling: Recently, available numerical or experimental data have been used to construct ROM operators [30] or to determine the unknown coefficients in classical ROM operators [3,11,32].…”
Section: Introductionmentioning
confidence: 99%
“…In our recent work [44], we have shown that this Correction term can be explicitly calculated and modeled with the available data by using the ROM projection as a spatial filter. We note that ROM spatial filtering has also been used to develop large eddy simulation ROMs, e.g., approximate deconvolution ROMs [45] and eddy viscosity ROMs [5,19,27,33,35,42]. In all these ROMs, it has been been assumed the differentiation and ROM spatial filtering commute:…”
Section: Introductionmentioning
confidence: 99%
“…Data‐driven ROMs (DD‐ROMs) (eg, sparse identification of nonlinear dynamics and operator inference method) use a fundamentally different strategy: they first postulate a ROM ansatz truea˙=trueA˜0.1embold-italica+a2.56804pttrueB˜0.1embold-italica, and then, they choose the operators trueA˜ and trueB˜ to minimize the difference between the FOM and ansatz , ie, mintrue-.8ptA^,1pttrueB^‖‖FOM(bold-italica˙A^abold-italicaB^a)2. Both Proj‐ROMs and DD‐ROMs are facing grand challenges : one of the main roadblocks for Proj‐ROMs is that they are not accurate models for the dominant modes. In practice, a corrected Proj‐ROM is generally used instead, ie, truea˙=A0.1embold-italica+a0.1emB0.1embold-italica+Correction. Thus, the ROM closure problem (ie, the modeling of the Correction term in ) needs to be addressed. DD‐ROMs, on the other hand, can be sensitive to noise in the data, since their operators trueA˜ and trueB˜ are obtained from an inverse problem …”
Section: Introductionmentioning
confidence: 99%